Bleeding and thrombotic complications during treatment with direct oral anticoagulants or vitamin K antagonists in venous thromboembolic patients included in the prospective, observational START2-register - Daniela Poli; Emilia Antonucci; Vittorio Pengo; Niccolò Maggini; Sophie Testa; Antonio Insana; Carmelo Paparo; Pasquale Pignatelli; Gualtiero Palareti; Paolo Prandoni; Elvira Grandone; Cristina Legnani; et al. (BMJ Open)
Objective The proportion and characteristics of Italian patients affected by venous thromboembolism (VTE) treated with direct oral anticoagulants (DOACs) or vitamin K antagonists (VKAs), and complications occurring during follow-up.Design A prospective cohort of 2728 VTE patients included in the Survey on anticoagulaTed pAtients RegisTer (START2-Register) from January 2014 to June 2018 was investigated. Characteristics of patients, type of treatment and complications occurring during 2962 years of follow-up were analysed.Setting About 60 Italian anticoagulation and thrombosis centres participated in the observational START2-RegisterParticipants 2728 adult patients with VTE of a lower limb and/or pulmonary embolism (PE), with a follow-up after the initial phase treatment.Interventions Patients could receive DOACs or VKAs; both prescribed by the National and Regional Health Systems for patients with VTE.Outcomes measures Efficacy: rate of VTE recurrence (all thrombotic complications were also recorded). Safety: the rate of major and clinically relevant non-major bleeding events.Results Almost 80% of patients were treated with DOACs. The prevalence of symptomatic PE and impaired renal function was higher in patients receiving VKAs. Duration of anticoagulation was >180 days in approximately 70% of patients. Bleeding events were similar in both treatment groups. The overall eventuality of recurrence was significantly higher in DOAC cohorts versus VKA cohorts (HR 2.15 (1.14–4.06), p=0.018); the difference was almost completely due to recurrences occurring during extended treatment (2.73% DOAC vs 0.49% VKA, p<0.0001). All-cause mortality was higher in VKA-treated (5.9%) than in DOAC-treated patients (2.6%, p<0.001).Conclusion Italian centres treat most patients with VTE with DOACs and prefer VKA for those with more serious clinical conditions. Recurrences were significantly more frequent in DOAC-treated patients due to increased incidence after 180 days of treatment, probably due to reduced adherence to treatment. These results underline the importance of structured surveillance of DOAC-treated patients with VTE to strengthen treatment adherence during extended therapy.